Existence of Solutions for a Baby-Skyrme Model - Hongan Hu; Kunlin Hu (Journal of Applied Mathematics)
The existence of the energy-minimizing solutions for a baby-Skyrme model on the sphere is proved using variational method. Some properties of the solutions are also established.